2010
DOI: 10.1111/j.1365-3156.2010.02611.x
|View full text |Cite
|
Sign up to set email alerts
|

First attempt to validate the gSG6-P1 salivary peptide as an immuno-epidemiological tool for evaluating human exposure to Anopheles funestus bites

Abstract: Summary Objective  The development of a biomarker of exposure based on the evaluation of the human antibody response specific to Anopheles salivary proteins seems promising in improving malaria control. The IgG response specific to the gSG6‐P1 peptide has already been validated as a biomarker of An. gambiae exposure. This study represents a first attempt to validate the gSG6‐P1 peptide as an epidemiological tool evaluating exposure to An. funestus bites, the second main malaria vector in sub‐Saharan Africa. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 15 publications
8
49
0
Order By: Relevance
“…gambiae and An . funestus bites [17,2427], and has been used to evaluate the efficacy of insecticide treated nets against malaria transmission [28]. In regard to Aedes species, the 34kDa salivary protein appears to be antigenic and specific to Aedes genus [2931].…”
Section: Introductionmentioning
confidence: 99%
“…gambiae and An . funestus bites [17,2427], and has been used to evaluate the efficacy of insecticide treated nets against malaria transmission [28]. In regard to Aedes species, the 34kDa salivary protein appears to be antigenic and specific to Aedes genus [2931].…”
Section: Introductionmentioning
confidence: 99%
“…20 Previous studies have shown that antibodies against vector salivary proteins can serve as markers for disease risk [21][22][23] and can be used to evaluate the efficacy of vector control efforts. 24,25 Our previous studies have shown increased antibody titers to salivary proteins in subjects with malaria or dengue, compared with subjects living in the same region but with no sign of infection. 21,22 There have been a number of studies validating the detection of anti-mosquito salivary proteins as biomarkers for mosquito bite exposure.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 There have been a number of studies validating the detection of anti-mosquito salivary proteins as biomarkers for mosquito bite exposure. 21,[24][25][26][27][28][29][30] Although the different studies have all used different methods to assess immune response to mosquito salivary proteins, all suggest that antibodies to mosquito salivary proteins are effective biomarkers for exposure.…”
Section: Introductionmentioning
confidence: 99%
“…gambiae and An. funestus in children living in malaria transmission area (Poinsignon et al 2008(Poinsignon et al , 2010. Further studies should investigate its potential to detect the exposure to An.…”
Section: The Peptide Approachmentioning
confidence: 96%